Business Strategies and Opportunities in the Digital Age - Muhammad Junaid Kamaruddin; Blegoh Andi Setya Utama (Economic, Management, Business and Accountancy International Journal, 2024)
The study aims to provide and obtain information about Business Strategies and Opportunities in the digital era. One of them is through Tiktok Shop for Generation Z. The research method uses qualitative with literature studies. Data sources come from several journal articles, YouTube, and online news, and interviews. The coding process and visualization of research results use NVivo Software. The research findings explain that the strategy and business opportunities at Tiktok Shop for generation z. The research results obtained five points of benefits obtained by generation z. The results of the study obtained five points of benefits obtained including the potential for Live Streaming, Relevant and Interesting Content for Business, Building Consumer Trust and Loyalty, Creative Promotion, and Collaboration with Influencers. With these five benefits, information about business strategies and opportunities at Tiktok Shop is expected to help and benefit generation z to start and open an online business on Tiktok.